2009
DOI: 10.1063/1.3083074
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of a-plane InGaN/GaN multiple quantum wells on r-plane sapphire substrates with different indium compositions

Abstract: In x Ga 1−x N / GaN ͑x = 0.09, 0.14, 0.24, and 0.3͒ multiple-quantum-wells ͑MQWs͒ samples, with a well width of about 4.5 nm, were achieved by utilizing r-plane sapphire substrates. Optical quality was investigated by means of photoluminescence ͑PL͒, cathodoluminescence, and time resolved PL measurements ͑TRPL͒. Two distinguishable emission peaks were examined from the low temperature PL spectra, where the high-and low-energy peaks were ascribed to quantum wells and localized states, respectively. Due to an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 21 publications
3
22
0
Order By: Relevance
“…Furthermore, while the DOLPs of a-plane quantum wells (QWs) are limited to ~0.60 [26], we report a much higher average DOLP of ~0.90 in a-plane InGaN QDs. Previous investigations have reported polarization properties of some a-plane InGaN QDs along [0001] [27], orthogonal to those reported in a-plane QWs (along ) [26,28,29]. We find that this is a special case to the general behavior of a-plane QDs.…”
Section: Introductionmentioning
confidence: 53%
“…Furthermore, while the DOLPs of a-plane quantum wells (QWs) are limited to ~0.60 [26], we report a much higher average DOLP of ~0.90 in a-plane InGaN QDs. Previous investigations have reported polarization properties of some a-plane InGaN QDs along [0001] [27], orthogonal to those reported in a-plane QWs (along ) [26,28,29]. We find that this is a special case to the general behavior of a-plane QDs.…”
Section: Introductionmentioning
confidence: 53%
“…Previous literatures have reported that the carriers could receive activation energy to thermalize from potential minima to nonradiative or delocalized centers as the temperature was increased. To get insight into the thermal quenching process associated with the localized states, the PL intensity as a function of temperature was studied, and the experimental temperature-dependent PL data were fitted by Arrhenius equation to investigate the carrier behavior during the thermal processes [14] IðTÞ…”
Section: Resultsmentioning
confidence: 99%
“…It means the InGaN/GaN MQWs grown on (1 1 0 1) GaN/7 degrees off axis (0 0 1) Si substrate have very low internal piezoelectric field and this leads to the decrease of QCSE [22]. The integrated PL intensity was fitted based on the relation I $ P a [23], where I is the integrated PL intensity, P is the excitation power density, and a is the power index. The fitting result is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%